Funding Urgency to Establish Energy Transition Mechanism Country Platform Through Green Bond Financial Instruments in Indonesia - Amalia Dewi Puspitasari; Dwi Elok Indriastuty (Budapest International Research and Critics University, 2023)
As a step towards pursuing the Net Zero Emission (NZE) target of 2060 or faster, Indonesia at the Bali G20 Summit launched the Energy Transition Mechanism (ETM) Country Platform. The formation of this ETM is one of the efforts to accelerate the energy transition from fossil energy to energy that is more environmentally friendly, namely by using New and Renewable Energy (EBT). One of the issues that have surfaced is related to the EBT funding scheme which requires a sizable fee. Currently, the Indonesian Capital Market has a new financial instrument called a green bond. The purpose of this study is to analyze the Green Bond financial instrument when viewed from a legal perspective as a source of financing for Renewable Energy in Indonesia. This research is normative research equipped with empirical data. This research is also a type of exploratory research. The approach used is the statutory approach and the conceptual approach. The results of the study show that Green Bonds are still regulated through the Financial Services Authority Regulation (POJK) Number 60 of 2017. However, to become a source of EBT financing, Green Bonds should be mentioned in the EBT Bill to provide legal certainty to investors who want to invest in EBT development in Indonesia.